The Development of Intensity Model on Technopreneurship to Improve Turnover in Micro, Small and Medium Enterprises (MSMEs) Culinary in Makassar, Indonesia - Andi Arifwangsa Adiningrat; Warda Warda (Yayasan Riset dan Pengembangan Intelektual, 2023)
This research designed and developed a intensity model based on technopreneurship-. This research is an applied research that aims to measure the practicality and measure the effectiveness of the form of the intensity model developed in entrepreneurship based on technopreneurship to increase MSME turnover. This research uses qualitative and quantitative methods. The research instrument was a questionnaire consisting of 4 types, namely: 1) used for instrument validation, 2) used for an initial study of the problems experienced by MSME actors, 3) for validating the developed model, 4) used during tryouts. Meanwhile, for the application of the developed model, interviews will be used about the achievement of entrepreneurship development to increase MSME turnover. The research subjects were Makassar typical culinary SMEs, selected incidentally, while the research participants were 2 experts in the fields of economics and technology as validators. Quantitative data analysis was carried out by calculating the percentage of respondents' answers, while qualitative data was analyzed by interpreting the answers from respondents about the practicality and effectiveness of the developed model. The results showed that the intensity model based on technopreneurship- is very practical for MSME to use and the intensity model has a very effective level of effectiveness in entrepreneurship so that it can increase the turnover of culinary UMKM typical of Makassar City.